Case Report: Mechanical thrombectomy using stent retriever devices in deep cerebral venous thrombosis: illustrative cases - Martínez-Martín, Álvaro; Hernández-Fernández, Francisco; Molina-Nuevo, Juan David; Serrano Serrano, Blanca; Segura, Tomás (Frontiers in Stroke, 2025)
BackgroundTreatment of cerebral venous thrombosis has traditionally been based on anticoagulant therapy. However, in certain circumstances, such as deep cerebral venous thrombosis, anticoagulation may be insufficient, so endovascular treatment by mechanical thrombectomy has been used for some years. There is currently no clear indication of which device is the gold standard in the endovascular treatment of cerebral venous thrombosis, although stent retriever devices are the most commonly used.Case presentationWe describe two cases of deep cerebral venous thrombosis refractory to anticoagulant treatment treated by mechanical thrombectomy with stent retriever devices, one of which has not been described to date as being used in the treatment of cerebral venous thrombosis (Tiger XL®).ConclusionsSome situations in like deep cerebral venous thrombosis may require endovascular treatment with mechanical thrombectomy if anticoagulation fails, with increasing evidence that it improves vital and functional prognosis.